2009
DOI: 10.1136/gut.2009.184176
|View full text |Cite
|
Sign up to set email alerts
|

Disease-related expression of the IL6/STAT3/SOCS3 signalling pathway in ulcerative colitis and ulcerative colitis-related carcinogenesis

Abstract: The importance of IL6/p-STAT3 in patients with inflammation-induced CRC was demonstrated. Moreover, SOCS3 may be involved in UC pathogenesis and the absence of SOCS3 seems critical for CRC progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
211
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(222 citation statements)
references
References 43 publications
7
211
0
4
Order By: Relevance
“…Interleukin-6 (IL-6), a pro-inflammatory cytokine, has been shown to regulate cancer cell growth and thereby contribute to tumor promotion and progression (5). has been demonstrated to be associated with an unfavorable prognosis in patients with various types of cancers including both sporadic and colitis-associated CRC (6). However, despite clear evidence implicating IL-6 in causation of CRC, molecular mechanisms underlying this phenomenon are still incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin-6 (IL-6), a pro-inflammatory cytokine, has been shown to regulate cancer cell growth and thereby contribute to tumor promotion and progression (5). has been demonstrated to be associated with an unfavorable prognosis in patients with various types of cancers including both sporadic and colitis-associated CRC (6). However, despite clear evidence implicating IL-6 in causation of CRC, molecular mechanisms underlying this phenomenon are still incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Li et al (2010) investigated the expression of IL-6 and its epithelial targets in patients with UC who had progressed to CRC. They found that the expression of both IL-6 and STAT3 was greater in both patients with active UC and those who had progressed to CAC, compared with both patients with inactive disease and control patients.…”
Section: Cytokinesmentioning
confidence: 99%
“…Although these studies imply a key role for STAT3 in mediating the potent anti-inflammatory effects of IL-10, the role of STAT3 in facilitating proinflammatory responses of IL-6 and other STAT3-activating cytokines remains ill-defined with current Stat3 gene knock-out mouse models. Moreover, considering persistent STAT3 activation is a feature of numerous human inflammatory diseases (e.g., human ulcerative colitis, RA) (25,26), there is a growing need for genetically defined mouse models displaying hyperactivated levels of endogenous STAT3 to investigate the mechanisms by which STAT3 promotes the pathogenesis of inflammatory diseases.…”
mentioning
confidence: 99%